Factors associated with and predicting anxiety in informal primary caregivers of children undergoing cancer treatment - Suárez-Rayo, Aline; Lara-Pompa, Nara Elizabeth; Villeda-Aguilar, Alejandra; Urrutia-Ballesteros, Isaac Manuel; Esmer-Sánchez, Carmen; Vega-Vega, Lourdes; Escamilla-Asiain, Gabriela; Méndez-Venegas, José (Psicooncología, 2024)
Objective: assess the presence of anxiety in informal primary caregivers of children with cancer within the first 6 months of treatment and identify the factors of caregivers (sociodemographic and psychological) and patients (sociodemographic and medical) associated with an predicting anxiety. Method: retrospective, descriptive, and cross-sectional study. Data from all caregivers of children diagnosed with cancer at the Teletón Children's Oncology Hospital were analyzed from June 2019 to December 2021. Caregivers of children with more that 6 months since diagnosis were excluded. They were evaluated using a questionnaire of sociodemographic and medical data, Beck Anxiety Inventory, Beck Depression Inventory II, Zarit Burden Interview, and Distress Thermometer. Descriptive, asssociation, relative risk, and prediction analyses were conducted. Results: A total of 91 caregivers were included in the study, among whom 71.4% presented anxiety. Significant associations (p
Keywords: anxiety; depression; burden; distress; caregivers; cancer; children